The Genetics of Racing Performance in Arabian Horses - K. Ropka-Molik; M. Stefaniuk-Szmukier; A. D. Musiał; B. D. Velie (International Journal of Genomics)
Arabian horses are commonly believed to be one of the oldest and most influential horse breeds in the world. The high financial benefits obtained from races tend to search for genetic markers strongly correlated with the results achieved. To date, the modern approaches such as transcriptome, miRNAome, and metabolome analyses have been used to investigate the genetic background of racing performance as well as endurance capacity in Arabians. The analysis of polymorphisms at the genome level has also been applied to the detection of genetic variants associated with exercise phenotype in the Arabian breed. The presented review summarizes these findings, with a focus on the genetics underlying flat racing and endurance performance traits in different Arabian horse populations.